Kyk, beleef of luister? Spiritualiteit in die Psalms in die lig van Psalm 1 en 2 - J. L. Helberg (In die Skriflig, 2005)
Look, experience or listen? Spirituality in the Psalms in the light of Psalm 1 and 2 A few approaches regarding spirituality are highlighted. An investigation is then made about what the psalms say regarding issues such as the following: in the training school of the Torah (Psalm 1), experience and creativity, vigour, complaint and praise, spirituality and enmity. Psalms 1 and 2, approached as introduction to the Psalter, show that the Torah (Law/Word) of the Lord occupies an all-important place in spirituality. Spirituality has especially to do with instruction and relations. Trust, joy and amazement combined with reforming self- discovery play an important role. One must commune with the Torah, and thus with God and also with one’s neighbour by listening and being involved. One must comply with the Torah in practical life and actively love one’s neighbour, especially the needy.